SOCIAL PSYCHOLOGICAL CHARACTERISTICS OF THE FORMATION OF LIFE VALUES IN STUDENTS - F. U. Sulaymanova (American Journals Publishing, 2023)
The article describes the social psychological characteristics of the formation of life values in students. It is emphasized that the study of the formation of the personal value system is one of the urgent tasks of modern psychology. During the research, it was found that the values of students are primarily focused on hedonistic, material and family values, and the status of spiritual, moral and aesthetic values is low.
Keywords: value, spirituality, desire, society, socialization, hedonism, psychological correction, questionnaire, behavior. Social psychological characteristics of the formation of social values in students